“It is always there in your face.” Australian young people discuss exposure to gambling activities and promotions. - Samantha Thomas; Simone McCarthy; Hannah Pitt; Sarah Marko; Sean Cowlishaw; Melanie Randle; Mike Daube (SSM: Qualitative Research in Health, 2023)
The normalisation of gambling for young people is a growing public health challenge. Despite initiatives aimed at reducing young people's exposure to unhealthy products, there is still little understanding of how they may be exposed to gambling. Using social exposure theory, this study aimed to explore young people's observations of gambling products and promotions within their everyday environments. In-depth interviews were conducted with 54 young people (n ​= ​25 girls, n ​= ​29 boys, aged 11–17 years) in Australia. Convenience and then snowball and purposive recruitment strategies were used to ensure a range of gambling attitudes and experiences were represented. Data were interpreted using reflexive thematic analysis. Young people described seeing gambling in varied social environments such as their own homes; physical environments in their local communities – including at local shopping centres, post offices, and sporting matches; and through symbolic environments such as marketing in community settings, on traditional and social media platforms, and depictions of gambling in movies and television shows. This exposure contributed to the perception that gambling was a normal activity, often placed alongside non-gambling activities in everyday settings. Comprehensive evidence-based public health strategies are needed to protect young people from exposure to gambling activities and promotions. These should include legislation to restrict the marketing and availability of gambling products, and research-based public education designed to counter normalising messages about gambling.